Peningkatan Kemampuan Guru Pendidikan Agama Islam dalam Melaksanakan Proses Pembelajaran melalui Supervisi Akademik Berbasis Teknologi Informasi dan Komunikasi - Thoyibah, Thoyibah (Paedagogie, 2021)
The purpose of this research is to improve the ability and skills of teachers in preparing lesson plans; manage learning process activities; utilizing information and communication technology; as well as a vehicle for improving the professionalism of teachers. This study uses the School Action Research (PTS) method. The model of this research uses cycles model that improved by Kemmis and Mc. Taggart. The subjects of this study were PAI teachers in the second semester of the 2019/2020 academic year in the Tanjung District, Brebes Regency, totaling 16 teachers.The results showed that through the use of academic supervision based on Information and Communication Technology, the ability of PAI teachers in Tanjung Subdistrict, Brebes Regency increased in quality learning by comparing the results of observations in the pre-cycle of 63.65% which was classified as lacking; the first cycle of 65.10% which is classified as less; and increased in the second cycle to 70.17% which is classified as less; and in the third cycle increased to 86.72% with good category. This method is expected to be a reference for teachers in teaching similar texts or other genres.